2016
DOI: 10.1016/j.clinph.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modulation of corticospinal excitability and short-latency afferent inhibition during onset and maintenance phase of selective finger movement

Abstract: Objective During highly selective finger movement, corticospinal excitability is reduced in surrounding muscles at the onset of movement but this phenomenon has not been demonstrated during maintenance of movement. Sensorimotor integration may play an important role in selective movement. We sought to investigate how corticospinal excitability and short-latency afferent inhibition changes in active and surrounding muscles during onset and maintenance of selective finger movement. Methods Using transcranial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This finding indicates that fast cortical sensory-to-motor interactions are blocked in relaxed surrounding muscle during tonic contraction of a single hand muscle. This finding confirms previous single-site TMS studies which show a dynamically modification of SAI during movement preparation and execution (Asmussen et al, 2014(Asmussen et al, , 2013Cho et al, 2016;Classen et al, 2000). The context-dependent loss of homotopic SAI and heterotopic SAF in the surrounding muscle during an isolated tonic contraction may have a stabilizing function for feedforward control of tonic contraction, rendering the M1 HAND less sensitive to transient sensory input from the hand.…”
Section: Context Dependency Of Center-surround Sensorimotor Integrationsupporting
confidence: 90%
“…This finding indicates that fast cortical sensory-to-motor interactions are blocked in relaxed surrounding muscle during tonic contraction of a single hand muscle. This finding confirms previous single-site TMS studies which show a dynamically modification of SAI during movement preparation and execution (Asmussen et al, 2014(Asmussen et al, , 2013Cho et al, 2016;Classen et al, 2000). The context-dependent loss of homotopic SAI and heterotopic SAF in the surrounding muscle during an isolated tonic contraction may have a stabilizing function for feedforward control of tonic contraction, rendering the M1 HAND less sensitive to transient sensory input from the hand.…”
Section: Context Dependency Of Center-surround Sensorimotor Integrationsupporting
confidence: 90%
“…, ; Cho et al . ). We recently reported that there is no significant relationship between afferent inhibition and tactile or motor performance (Turco et al .…”
Section: Discussionmentioning
confidence: 97%
“…J Physiol 596.21 movement planning (Voller et al 2005(Voller et al , 2006Richardson et al 2008;Ni et al 2011;Asmussen et al 2013Asmussen et al , 2014Cho et al 2016). We recently reported that there is no significant relationship between afferent inhibition and tactile or motor performance (Turco et al 2018b).…”
Section: Functional Relevance Of Afferent Inhibitionmentioning
confidence: 99%
“…In healthy individuals, SAI is consistently expressed at rest, but attenuated during finger movements (Dubbioso et al, 2017c). In the active target muscle, SAI was reduced at movement initiation during both mixed and homotopic cutaneous nerve stimulation (Asmussen et al, 2013; Cho et al, 2016), whereas SAI was reduced during the maintenance phase of the movement (Asmussen et al, 2013) or found to be normal (Cho et al, 2016). Accordingly, SAI and SAF by homotopic or heterotopic stimulation were abolished during the tonic contraction of the target muscle (Dubbioso et al, 2017c).…”
Section: Short-latency Afferent Inhibition In the Healthy Human Brainmentioning
confidence: 99%